(untitled) (Forum for Linguistic Studies, 2024)
This research deals with (Monitoring Iraqi Newspapers for the Role of Tunisian Lawyers and Professional Unions in the Events of the Revolution from December 17, 2010, to January 14, 2011). The lawyers and professional unions played a vital role in success the Tunisia revolution that was happened in Sayedi Bor Zaid. They supported the revolution for the first moment by effective speech and issues that storm the feelings of people and ordered the president Zain AlAbdean Bin Ali to be away from the head of the country and bring jobs for the jobless guys. These demonstrations changed ended with the leaving the president the head of the order in Tunisia.